The Chinese Junk Keying and American Racialization of Chinese - Zhang, Tao (American Studies in Scandinavia, 2019)
As the first Chinese wooden boat that ever reached the United States, the Keying, with its 40 Chinese sailors who composed the hitherto largest group of Chinese in America, not only satisfied Americans’ curiosity at Chinese junks and Chinese people, but prompted a nationwide attempt at racializing Chinese from 1847 to 1848. This prototypical Chinese racialization features a configuration in which Chinese were triangulated vis-a-vis American whites and nonwhites. Whites occupied the upper corner of the triangle, commanding discursive tools of mass publications to position Chinese relative to whites themselves and other minority groups on America’s racial ladder. Chinese were defined as an inferior, pitiable racial other that resembled Indians in appearance and stood somewhere in between Mexicans and blacks in terms of racial advancement. The triangular paradigm continued to function in American racialization of Chinese even after the departure of the Keying for Britain in February 1848, though with noticeable modifications.